Gender equity in intercollegiate athletics. - Illinois. Board of Higher Education ([Springfield, Ill.] : State of Illinois Board of Higher Education, 2005)
" ... presented in accordance with the state statute, which authorizes institutions of higher education in Illinois to grant tuition waivers for the purpose of attaining gender equity in intercollegiate atheletics. " -- Summary.
"June 7, 2005."
Title from caption.
Mode of access: Internet.
Keywords: Sex discrimination in sports -- Illinois; Women athletes -- Illinois; College sports -- Illinois